2019
DOI: 10.1186/s12879-019-3742-8
|View full text |Cite
|
Sign up to set email alerts
|

The impact of homocysteine, B12, and D vitamins levels on functional neurocognitive performance in HIV-positive subjects

Abstract: BackgroundThe correlation among high levels of total homocysteine, low levels of B12vitamin, and neurocognitive impairment in HIV negative patients has been the main research topic in some of the latest reviews. The aim of this study was to examine if the alteration of homocysteine, B12 vitamin, and D vitamins plasma levels was present in HIV-positive, and their relationship with cognitive function.Methods57 HIV infected were enrolled and underwent the serum measurement of homocysteine, B12, and D vitamins. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 27 publications
2
7
0
1
Order By: Relevance
“…Hyperhomocysteinaemia and vitamin B12 deficiency are often detected in patients affected with diseases associated with neuropathy such as diabetes, 66 alcoholism, 67 Parkinson’s disease (treated with L‐dopa), 68 or HIV infection 69 . Vitamin B12 deficiency could be a modifiable risk factor for neuropathy in those patients.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperhomocysteinaemia and vitamin B12 deficiency are often detected in patients affected with diseases associated with neuropathy such as diabetes, 66 alcoholism, 67 Parkinson’s disease (treated with L‐dopa), 68 or HIV infection 69 . Vitamin B12 deficiency could be a modifiable risk factor for neuropathy in those patients.…”
Section: Discussionmentioning
confidence: 99%
“…folate or vitamin B12 deficiency) 17 . It has been reported that vitamin B12 or folate 8 deficiency was the cause in two thirds of patients with hyperhomocysteinemia studied. The vitamin B12-dependent enzyme methionine synthase catalyzes the transfer of the methyl group from N-5-methyl-tetrahydrofolate to Hcy to form methionine.…”
mentioning
confidence: 98%
“…Homocysteine (Hcy), which has caught the attention of researchers and clinicians in recent years, is a recognized biomarker and an established independent risk factor for various diseases 1 , including cardiovascular disease (CVD) [2][3][4][5][6] , neurocognitive disorders 7,8 and osteoporotic fracture 9,10 .…”
mentioning
confidence: 99%
“…Thiamine deficiency is associated with episodic memory deficit and ataxia (Fama et al, 2019; Mulholland, 2006) and underlies Wernicke’s encephalopathy in both AUD and PLWH (Le Berre et al, 2019; Martin et al, 2003). The pattern of nutritional deficiencies in PLWH is wider, and in particular, B12 and D vitamin deficiencies have been linked to worse executive function and psychomotor speed among PLWH (Falasca et al, 2019). Specific profiles of deficiency associated with HIV/AUD are not yet established.…”
Section: Other Comorbiditiesmentioning
confidence: 99%